Two new species of the genus Phobeticomyia from China (Diptera, Lauxaniidae) - Shi, Li; Li, Wenliang; Yang, Ding (Zootaxa, 2009)
The following two species are described as new to science: Phobeticomyia digitiformis sp. nov. and Phobeticomyia uncinata sp. nov.. Phobeticomyia spinosa Sasakawa is newly recorded for China. A key to separate these species is presented.